A STUDY TO EVALUATE THE EFFECTIVENESS OF IEC CAMPAIGN ON SELF EFFICACY, HEALTH BEHAVIOUR AND THE REGULARITY OF DOTS THERAPY FOR EMPOWERMENT OF TB PATIENTS IN SELECTED TUBERCULOSIS UNITS, CHITTOOR DIST,ANDHRAPRADESH - JULIET K; FATHIMA LATHEEF (International Journal of Pharma and Bio Sciences, 2016)
The aim of the study was to evaluate the effectiveness of IEC (Information Education and Communication) campaign on self efficacy, health behavior and regularity of DOTS therapy for the empowerment of TB patients. True experimental design was adopted for this study. 20 adult tuberculosis patients were selected from Arogyavaram TB Sanatorium Chittoordist, Andhra Pradesh. Based on simple random sampling technique, 10 samples were allotted to each in experimental and control group. For both experimental and control groups, routine treatment was given (height, weight and sputum analysis). For the experimental group the intervention (Information Education and Communication) was administered. The post test overall mean value of self efficacy, health behavior and the regularity of DOTS therapy was found to be higher than the pretest value. The ‘t’ value for self efficacy, health behavior and the regularity of DOTS therapy between the post test assessment of experimental and control group was found to be 5.47,4.98 &4.77 respectively. It was found to be highly significant at p<0.001. Therefore the study concludes that the IEC campaign was effective in improving the self efficacy, Health behavior and the regularity of DOTS therapy among TB patients.